Indianidade, territorialidade e cidadania no período pós-independência – Vila de Itaguaí, 1822-1836 - Moreira, Vania (Diálogos Latinoamericanos, 2011)
The purpose of this paper is to analyze the transition of the indigenous colonial debate towards an actual national one, beginning after Brazil‟s independence in 1822, when Indians‟ rights and duties were being redefined in concordance with the new social and political order. The emphasis will be on the reaction of the new regime to the Indians of the Itaguaí village, who, after the promulgation of the Constitution in 1822, were considered as citizens, and thereafter enrolled as recruits in two troops of the National Guard. For reasons that seem strange from a legal point of view, they were deprived of the right to legally own the land they had received during the Colonial period.